Reynaldo Alarcon contribution to development and strengthening of psychometrics in Peru - León, Ramón (2009)
In this communication the author reviews the contributions of Reynaldo Alarcón to the psychometric tradition in the psychology of Peru. A former student of Walter Blumenfeld, the German psychologist emigrated to Peru in the 1930´s, Alarcón is author of a number of investigations in which he standardized questionnaires and inventories and intelligence tests, and explored aspects of the mentality of Peruvians. His text on research techniques and designs is a book of excellent quality. In the frame of this communication the author comments Alarcón’s interest for positive psychology, and his recent papers on psychology of happiness.